Diversity of arthropods subservient to olive groves in arid region (Northeastern Algeria) - MIMECHE, Hayet; CHAFAA, Smail; LAABASSI, Ayache (Studia Universitatis Babeș-Bolyai Biologia, 2024)
Olea europaea L. 1753, is one of the oldest and most distinctive trees in the Mediterranean region. Its nutritional, social, cultural, and economic value is very important for populations in arid regions, where it is widely distributed. A sign of a sustainable environment in many agricultural regions is the existence of a wide variety and abundance of arthropod groups. The main objective of the study is to evaluate the diversity of arthropods subservientin in olive agro-systems in the arid region by using several sampling techniques, namely classic sight hunting, visual inspection, Barber pots, and yellow traps. The inventory is carried out over a period of 5 months, from February to June 2023, in three stations in M’Sila (northeastern Algeria). Three classes of arthropods were found: Insecta, Arachnida, and Malacostraca. Captures were numerically dominated by Insecta, representing 96.88% of total captures. Arachnida and Malacostraca classes represented about 2.74 and 0.38%, respectively. During this research, a total of 1861 arthropod individuals were collected and identified into 83 species, 79 genera, 53 families, and 15 orders. The most abundant orders were: Diptera (42.56%), Hymenoptera (28.11%), and Coleoptera (7.32%). However, we found a significant difference in species composition according to habitat (P < 0.01). The species were determined, and the ecological indices were calculated (Shannon Value, Evenness values and Simpson reciprocal index). The dominant functional feeding groups were phytophages (41.91 %), predators (32.94%), and polyphages (22.14%). The arthropods included several olive pests such as Euphyllura olivina (Costa) (Hemiptera: Liviidae), Bactrocera oleae (Rossi) (Diptera: Tephritidae), Prays oleae (Bernard) (Lepidoptera: Praydidae), Liothrips oleae Costa (Thysanoptera: Phlaeothripidae), and Oxycenus maxwelli (Keifer) (Arachnida: Eriophyidae). Article history: Received 08 March 2024; Revised 26 April 2024; Accepted 10 June 2024; Available online 30 June 2024.